Manifesting the Spirit of “Gotong-Royong” between State Institutions in Maritime Security: As an Effort to Regulate and Enforce Law in Indonesia - Tarigan, Muhammad Insan; Hafandi, Raisha; Hakim, Dani Amran (As-Siyasi: Journal of Constitutional Law, 2025)
Maritime security is a major problem in Indonesia, with issues including maritime delimitation, IUU Fishing, piracy and robbery, and terrorism at sea. Nevertheless, the state’s maritime security system continues to face challenges with overlapping authority, competing sectoral interests, and conflicting laws and regulations. Moreover, it is important to be aware of the phenomenon of the fading value of gotong-royong as the essence of Pancasila contained in the preamble of the 1945 Constitution of the Republic of Indonesia. This investigation seeks to scrutinize the spirit of gotong-royong in the regulations as well as institutions of marine security guards as an attempt to negotiate the overlapping authorities and the intersection of laws and regulations of each authority. This research was conducted using juridical-normative method through literature study and conceptual approach. The concept of gotong-royong has not been fully embraced by maritime security authorities in Indonesia. It manifests itself through jurisdictional overlaps, sector egos, lack of clear coordination, and fragmentation among various agencies charged with enforcing maritime security. This study contends using the spirit of “gotong royong” and the empowerment of coastal people can enhance a maritime safety framework in Indonesia. This can be achieved through regional and global cooperation with partner countries to dispel potential threats to regional seas. Additionally, the capacity of coastal communities can be strengthened through the state defense program to contribute to maintaining maritime security in Indonesia. The Constitution of the Republic of Indonesia stipulates that all citizens have a mandatory obligation to engage in state defense.